Presenting Symptoms of Chiari Type I Malformation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Clinical and radiographic predictors of neurologic symptoms were investigated in a population-based retrospective study of 51 children identified with Chiari I malformation at the University of California, and Kaiser Department of Radiology, San Francisco.